Biocompatibility of NiTi alloys in the cell behaviour - Sevcikova, Jana; Pavkova Goldbergova, Monika (BioMetals, 2017)
Metallic biomaterial alloys composed of nickel and titanium have unique thermal shape memory, superelastic, and high damping properties, which are widely used in the medicine. The major parameter evaluated in the studies regarding the behaviour of the material in the contact with organism or cells is biocompatibility. The aim of the studies is to clarify the differences in the proliferation, growth, and morphology especially in the cell cultures. The cytotoxicity is affected among other by release of the metal ions in the presence of the metal alloy, which is further dependent on the possible treatments of the material and the corrosive properties. To evaluate the cytotoxicity, wide range of tests including the Sulforhodamine B assay and MTT tests, expression profiles, cell survival tests such as apoptotic test are used. The review compares the cell behaviour in contact with the material alloys composed of nickel and titanium with respect to different materials composition and different surface treatment that affects the ion release. Even though the results published so far are controversial, almost all data suggest sufficient biocompatibility in medical use.
Keywords: Cell Survival; tuková tkáň; Humans; viabilita buněk; Myocytes, Smooth Muscle; krysa rodu Rattus; lidé; zvířata; proliferace buněk; Cells, Cultured; titan; Human Umbilical Vein Endothelial Cells; apoptóza; Biocompatible Materials; Stem Cells; nikl; rhodaminy; Rhodamines; Titanium; myocyty hladké svaloviny; kultivované buňky; endoteliální buňky pupečníkové žíly (lidské); Cell Proliferation; Nickel; nádorové buněčné linie; Rats; biokompatibilní materiály; kmenové buňky; Animals; Cell Line, Tumor; Adipose Tissue; Apoptosis